The Sonogashira Carbonylation Reaction between Aromatic Bromide and Alkyne with N‐Formylsaccharin as a CO Source. Issue 22 (9th June 2022) - Tan, Yan; Lang, Jia‐Jia; Chen, Li‐Mei; Tang, Mei‐Lun; Yu, Zhi‐Xing; Mi, Peng‐Bing; Zheng, Xing
Abstract: The carbonylative Sonogashira coupling reaction of aromatic bromide with terminal alkynes has been developed with N ‐formylsaccharin as a CO source. The reaction, which has certain advantages in cost and safety of raw materials, is carried out in a simple and safe one‐pot method. A variety of alkynones with good functional group compatibility can be obtained in medium to high yields. Abstract : The carbonylative Sonogashira coupling reaction of aromatic bromide with terminal alkynes by using N ‐formylsaccharin as a CO source to synthesize a variety of alkynones compounds with good functional group compatibility. It is a low‐cost and safe method to obtain alkynone.